Are children with childhood apraxia of speech a subgroup of children with developmental coordination disorders? - Knežević, Dora (Array, 2019)
Motor development is related to various aspects of human development, from speaking to taking care of oneself and participating in sports. Developmental disorder affecting the motor domain is known as Developmental Coordination Disorder (DCD), which results in a marked impairment in motor skills, which in turn can have a significant impact on activities of everyday living (American Psychiatric Association, 2013). Several studies have shown that the motor deficit in DCD is not restricted to limb control and may be a more general phenomenon that could affect the speech motor system (Ho and Wilmut, 2010). According to Maassen (2002), there is strong evidence that delayed or deviant motor development and perceptual motor learning play a role in many children with childhood apraxia of speech (CAS). Knowing that articulation is a mechanical act executed by the complex speech apparatus, could this potentially mean that children with CAS are a subgroup of children with DCD? Different studies demonstrated that children with CAS had problems with various aspects of nonspeech oral motor function (Tükel, Björelius, Henningsson, McAllister and Eliasson, 2015), as well as balance, aiming and catching (Iuzzini-Siegel, 2019). Further evidences of impaired motor skills could help us understand the underpinnings of CAS.